INFLUENCE OF BUILDING FORM OF HOSPITAL ON ITS ENERGY PERFORMANCE - Shchuchenko, Vladyslav; Lie, Bernt; Harsem, Trond Thorgeir (European Scientific Journal, ESJ, 2014)
In this study thermal performance of hospital buildings with various geometries is examined. The aim of the work is to study the impact of the hospital building geometry on the total energy consumption. Three types of buildings are investigated – an arcade with glazed roof, a pavilion and a tower on a base (or in some literature called "matchbox on a muffin"). These hospital geometries (with some degree of deviation) are most commonly used in healthcare. The hospital geometries were simulated in several steps: beginning from existing (base case) hospital and further applying energy measures to achieve low energy hospital (with better insulated building body and demand controlled ventilation and lighting). The latter type is in its emerging phase and will be more and more in focus as authorities implement stricter building codes and as the demand on energy effective buildings rises continuously. The area of the modeled hospital is about 96 500 m2. The model represents an "average" large university hospital in Norway. Occupancy, schedule, internal gains, ventilation rates and fabric data are kept constant for each of the simulated cases. Influence of the hospital geometry in moderate and polar climate were also investigated. Building envelope data and technical systems data have been varied during the simulation in order to see how big influence has geometry on existing and low energy hospitals. Building models are simulated using Simien building energy and indoor climate software [1]. The results of this study show that, in general, geometry of the hospital building has very little influence on its energy use.